WACANA PENYINTAS KEKERASAN SEKSUAL DALAM PERSPEKTIF KRITIS tirto.id - Suprihatin, Suprihatin; Lestari, Rizky Nindy (Jurnal Nomosleca, 2019)
Â  Abstract The issue of violence against women can be found in abundance within the mass media news. Quoting the Indonesiaâ€™s National Committee on Violence Against Women (National Committee of Women) in 2017, there were 348,446 cases of violence against women. The data from National Committee of Women shows that there is a high percentage of sexual abuse within the domain of domestic or personal violence as well as community and public violence. The volume of news related to sexual abuses have been rising ever since the Police-General Tito Karnavian gave a controversial statement in October of 2017. As quoted from BBC Indonesia in an exclusive interview with Tito Karnavian, Tito said that in cases of rape accusations, the police sometimes must ask if the victim feels comfortable. This statement sparked a reaction from the public. Women activists highlighted Titoâ€™s statement and consider the questions to be insensitive because they ignore victimsâ€™ psychological condition. Online news portal Titro.id actively discuss the development of Titoâ€™s controversial statement. Not only does Tirto.id presents the news on the subject matter, they also conduct deep investigations involving both parties: the police force and the survivors of sexual abuses. Tirto.id was also present in a funding night to support the work of sexual abuse survivors in 11 November 2017 in Kantor Dagang Serikat Islam, Central Jakarta. The report was written by a journalist of Tirto.id in the â€œIn Depthâ€ rubric or exhaustive reports in the form of information gathered from attending the event. In order to research this topic, the researcher used the critical discourse analysis technique. This research will be analyzed using Norman Faircloughâ€™s scalpel. The outcome of this research shows that, within the textual analysis, both lexically and grammatically, Tirto.id uses dictions that imply supportive attitude towards the victims and survivors of sexual abuse, for example, the use of â€œtegasâ€ or â€œfirmâ€. Tirto.id also chooses negative adjectives such as â€œbereaksi kerasâ€ (â€œreacted violentlyâ€) and â€œperilaku kasar bahkan kejamâ€ (â€violent or even cruel behaviorâ€) to be associated with the perpetrators of sexual violence. The use of active sentences indicates that Tirto.id reinforces the presence of actors of sexual violence from the text. Which often media ignored when reported of sexual violence. Keywords: Critical Discourse Analysis, Norman Fairclough, news, sexual abuse.DOI:Â https://doi.org/10.26905/nomosleca.v5i2.3409